Bone Structural Similarity Score: A Multiparametric Tool to Match Properties of Biomimetic Bone Substitutes with their Target Tissues. Issue 3 (July 2016) - Falvo D'Urso Labate, Giuseppe; Baino, Francesco; Terzini, Mara; Audenino, Alberto; Vitale-Brovarone, Chiara; Segers, Patrick; Quarto, Rodolfo; Catapano, Gerardo
Background: One of the hardest tasks in developing or selecting grafts for bone substitution surgery or tissue engineering is to match the structural and mechanical properties of tissue at the recipient site, because of the large variability of tissue properties with anatomical site, sex, age and health conditions of the patient undergoing implantation. We investigated the feasibility of defining a quantitative bone structural similarity score based on differences in the structural properties of synthetic grafts and bone tissue. Methods: Two biocompatible hydroxyapatite porous scaffolds with different nominal pore sizes were compared with trabecular bone tissues from equine humerus and femur. Images of samples' structures were acquired by high-resolution micro-computed tomography and analyzed to estimate porosity, pore size distribution and interconnectivity, specific surface area, connectivity density and degree of anisotropy. Young's modulus and stress at break were measured by compression tests. Structural similarity distances between sample pairs were defined based on scaled and weighted differences of the measured properties. Their feasibility was investigated for scoring structural similarity between considered scaffolds or bone tissues. Results: Manhattan distances and Quadrance generally showed sound and consistent similarities between sample pairs, more clearly than simple statistical comparison and with discriminating capacity similar to image-based scores to assess progression of pathologies affecting bone structure. Conclusions: The results suggest that a quantitative and objective bone structural similarity score may be defined to help biomaterials scientists fabricate, and surgeons select, the graft or scaffold best mimicking the structure of a given bone tissue.